If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3n + 2) = 2(n + 10) Reorder the terms: 3(2 + 3n) = 2(n + 10) (2 * 3 + 3n * 3) = 2(n + 10) (6 + 9n) = 2(n + 10) Reorder the terms: 6 + 9n = 2(10 + n) 6 + 9n = (10 * 2 + n * 2) 6 + 9n = (20 + 2n) Solving 6 + 9n = 20 + 2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2n' to each side of the equation. 6 + 9n + -2n = 20 + 2n + -2n Combine like terms: 9n + -2n = 7n 6 + 7n = 20 + 2n + -2n Combine like terms: 2n + -2n = 0 6 + 7n = 20 + 0 6 + 7n = 20 Add '-6' to each side of the equation. 6 + -6 + 7n = 20 + -6 Combine like terms: 6 + -6 = 0 0 + 7n = 20 + -6 7n = 20 + -6 Combine like terms: 20 + -6 = 14 7n = 14 Divide each side by '7'. n = 2 Simplifying n = 2
| 49x^2+4x-8=7x | | (0.018+b)*0.01=0.018 | | a^2+a+1=0equation | | a^2+a-1=0equation | | 2/3n-3/5n=1 | | 5/2x-7/2y=-1 | | 3(-3n+4)+6n=12 | | 5n=3(n+12) | | z^2+(4+2i)z+3-3i=0 | | x-2/135 | | 8c-9=-129 | | y/1-y | | 7=In(x+9) | | 8x+y=11+7y | | 1y=8-3y | | 2(x+4)=2(10x+1) | | x^2-5kx+5k-1=0 | | 3x=0.10-x | | 5xt-2xt= | | z^4=4i | | 3p+2q=5 | | x/5=36/20 | | x/4-2/5 | | 3.67=log(x) | | 4d+3=d-6 | | 2m-6=m+2 | | x^2-x-1=2x+1 | | X^2+28x=16 | | 12-(5x+3)+7(x+1)=8-2x | | logx=-0.45 | | 60+-25x=35x+20 | | t^2-5t-5=0 |